Penerapan Target Costing Dan Activity Based Costing Sebagai Penentuan Biaya Produksi Pada UMKM Larasati Jakarta - Kaila, Azizah apriliani putri; Meidinata, Istiqamah; Cicilya, Jesicha; Ziyah, Salsabila; Lestari, Tri (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
Determining the costof production is an important aspect in the sustainability and competitiveness of a business, especially in the micro, small, and medium enterprises (UMKM) Sector. This study aims to analyze the application of the Target Costing and Activity Based Costing methods in determining production costs at the mie ayam larasati. The research method uses a qualitative approach with data collection techniques through direct interviews with business owners. The result of the study indicate that the use of the Target Costing and Activity Based Costing methods can provide a more accurate picture of cost, as well as help determining selling prices that are in accordance with market conditions and production costs with the Target Costing system lower that the calculation of Activity Based Costing costs